HUBUNGAN BERAT BADAN IBU HAMIL DENGAN KEJADIAN PREEKLAMPSIA DI RUMAH SAKIT UMUM DAERAH dr. ZAINOEL ABIDIN BANDA ACEH - Syahbandi Syahbandi; Eulisa Fajriana; Sirajul Muna (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2021)
High risks in pregnancy can caused by uncontrolled increasing body weight in pregnancy. It can affect on maternal or fetal. Risk on maternal such as pre eclampsia, gestational diabetes and increase of labor with section secarea. Risks on fetal are risiko macrosomia, obesity in baby, preterm baby or delivery less than 37 weeks of pregnancy. A retrospective study was conducted among 132 pregnant women with pre eclampsia in dr. Zainal Abidin Banda Aceh hospital on August 2021. Data collected using checklist.In the analysis of the data, Chi Square analysis was used. The result found that 97 respondents ( 73,5 % ) are pregnant women with mild pre eclampsia. The body weight of 71 respondents (53,8 %) increased abnormally on pregnancy. 31 respondents from 71 respondents who had increase their body weight were severe pre eclampsia pregnants women. There were significant correlation between increasing body weight and pre eclampsia in dr. Zainoel Abidin Banda Aceh hospital. Suggestion of the the research is midwife can give counseling about normal limit of body weight gain in the pregnancy dan pre eclampsia in pregnancy